1) 2x² - 5x + 3 = 0; D = 25 - 24 = 1; √D = 1; x₁ = (5 + 1)/4 = 1,5; x₂ = (5 - 1)/4 = 1
2x² - 5x + 3 = 2(x - 1,5)(x - 1) = (2x - 3)(x - 1).
ответ: 2x² - 5x + 3 = (2x - 3)(x - 1).
2) x² - 11x + 30 = 0; x₁ = 5; x₂ = 6.
x² - 11x + 30 = (x - 5)(x - 6).
ответ: x² - 11x + 30 = (x - 5)(x - 6).
1) 2x² - 5x + 3 = 0; D = 25 - 24 = 1; √D = 1; x₁ = (5 + 1)/4 = 1,5; x₂ = (5 - 1)/4 = 1
2x² - 5x + 3 = 2(x - 1,5)(x - 1) = (2x - 3)(x - 1).
ответ: 2x² - 5x + 3 = (2x - 3)(x - 1).
2) x² - 11x + 30 = 0; x₁ = 5; x₂ = 6.
x² - 11x + 30 = (x - 5)(x - 6).
ответ: x² - 11x + 30 = (x - 5)(x - 6).